2020
DOI: 10.3390/ma13030687
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia Reduced Graphene Oxide Nano-Hybrid Structure Fabricated by the Hydrothermal Reaction Method

Abstract: In this work, we report an available technique for the effective reduction of graphene oxide (GO) and the fabrication of nanostructured zirconia reduced graphene oxide powder via a hydrothermal method. Characterization of the obtained nano-hybrid structure materials was carried out using a scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and Fourier-transform infrared spectroscopy (FTIR). The confirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…It is observed that the intensity of the D band is lower than that of the G-band, which confirms the reduction of GO to rGO. After the incorporation of IL, few peaks are shifted and appear at 172, 254, 302, 442, 463, 633, and 1336 (D-band) and 1599 cm –1 (G-band) in ZrO 2 -rGO-IL ( I D / I G = 0.85) that confirms the successful binding of IL with ZrO 2 -rGO. ,, …”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…It is observed that the intensity of the D band is lower than that of the G-band, which confirms the reduction of GO to rGO. After the incorporation of IL, few peaks are shifted and appear at 172, 254, 302, 442, 463, 633, and 1336 (D-band) and 1599 cm –1 (G-band) in ZrO 2 -rGO-IL ( I D / I G = 0.85) that confirms the successful binding of IL with ZrO 2 -rGO. ,, …”
Section: Resultsmentioning
confidence: 70%
“…The synthesis of the ZrO 2 -rGO nanocomposite has been done via a one-step hydrothermal method with some modifications. , Briefly, a 0.2 M ZrOCl 2 .8H 2 O was mixed in 25.0 mL of milli-Q water and then sonicated for 30 min for complete dispersion of zirconium salt. Subsequently, 5.0 mL GO (10.0 mg mL –1 ) was mixed in 20 mL of milli-Q water.…”
Section: Methodsmentioning
confidence: 99%
“…The FTIR spectra of the calcined fibers show only bending and stretching vibrations of -OH groups originating from coordinated or readsorbed water at 3300, 1575 and 1405 cm −1 and Zr-O vibrations at 750 cm -1 and below 500 cm -1 . [14,40,41] The absence of IR peaks of organic groups confirms the purity of the synthesized products that is essential for the uptake properties of the material as organic residues could cover active surface sites of ZrO 2 .…”
Section: Tgamentioning
confidence: 84%
“…), and which require high precision. Moreover, these forming methods need the manufacture of molds and post-processing, which is time-consuming and costly [ 41 , 42 ]. Meanwhile, AM technologies such as powder-, slurry- and bulk solid-based techniques are promising methods for producing near net complex shape parts and consequently allows for saving time and reducing production costs of required products in comparison with traditional forming methods.…”
Section: Additive Manufacturing Processes For Ceramic and Their Prmentioning
confidence: 99%